The development of Nahwu Science in the Development of Modern Linguistics - Hasani, M. Ahsanul; Muhaimin; Najmuddin, Muhammad Alim (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Nahwu science, as a branch of Arabic language that studies sentence structure and the relationship between its elements, has a significant influence on the development of modern linguistics. This study aims to analyze the contribution of Nahwu science to the development of current linguistic theory and practice. Basic concepts in Nahwu, such as i’rab (case markers), sentence types, and sentence structures, can provide insight into understanding the grammar and syntax of various languages. In addition, Nahwu science also plays a role in the formation of generative grammar theory and structural analysis of language, which provide a foundation for comparative linguistic studies. Understanding the principles of Nahwu also contributes to the translation and interpretation of classical and modern texts, and helps in deeper analysis of meaning in semantic studies. This study uses a content analysis method with a qualitative descriptive approach, reviewing various sources such as journals, articles, websites, and books that discuss the relationship between Nahwu and modern linguistics. The analysis is carried out by examining the main concepts in Nahwu and comparing them with modern linguistic theory. The results of the study are expected to enrich the understanding of the relationship between the science of Nahwu and contemporary linguistic theory, as well as provide significant contributions to the development of Arabic and other language studies in a global context. Thus, this study confirms that the science of Nahwu is not only relevant in traditional Arabic studies, but also has a major impact on the development of modern linguistics in general.